Solving faculty-course allocation problem using integer programming model - Torres, Monica C.; Villegas, Kyla Kiela S.; Gavina, Maica Krizna A. (Vol.150, N0.4 (August 2021) pages 679-691.)
"One of the most challenging tasks performed by the department chair every semester is the assignment of faculty members to course. This task, when done manually, is tedious to accomplish because of the numerous faculty-course combinations, the policies to be considered, faculty retirements, faculty resignations, and the hiring of faculty members. Satisfying the needs of employees has been increasingly significant in the scheduling decisions of different companies. In this study, a binary integer programming model that considers the preferences of faculty members was proposed to solve the faculty-course allocation problem"-Title page.